Repetitive transcranial magnetic stimulation combined with respiratory muscle training for pulmonary rehabilitation after ischemic stroke—A randomized, case-control study - Cao, Haiyan; Chen, Xiaoming; Ren, Xuyan; Chen, Zhiguo; Liu, Chuandao; Ni, Jianqiang; Liu, Haoyu; Fan, Yingjie; Xu, Dandan; Jin, Huaping; Bao, Jie; Yulun, Huang; et al. (Frontiers in Aging Neuroscience, 2022)
Respiratory muscle weakness often occurs after stroke, which can lead to pulmonary dysfunction (PD). Pulmonary dysfunction prolongs the length of hospital stay and increases the risk of death. In a prospective, randomized, case-control study, we used musculoskeletal ultrasonography (MSUS) and lung functional test instrument to objectively evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) combined with respiratory muscle training (RMT) in the treatment of PD in patients with acute ischemic stroke. 60 Stroke patients with PD were recruited and randomized into two groups. The control group was treated with RMT, and the treatment group was trested with rTMS on the basis of RMT. Treatment occurred five times a week for 8 weeks.Before and after treatment, diaphragmatic thickness(DT), diaphragmatic thickening fraction(DTF) and diaphragmatic mobility(DM) in patients, bilateral chest wall were measured by MSUS. Meanwhile, FVC, FEV1, FEV1/FVC, PEF and MVV tested by lung functional test instrument were used to evaluated the improvement of lung functional. ADL was used as an objective criterion to evaluate the overall functional recovery of patients before and after treatment.After treatment, DT, DTF, and DM values improved significantly in both the affected and unaffected sides.The FVC, FEV1, FEV1/FVC, PEF, MVV and ADL were all increased after the treatment. Combined treatment showed a stronger increase than that by RMT treatment alone. The study preliminarily shows that rTMS and RMT could improve lung functional after acute ischemic stroke.